(untitled) (Research, Society and Development, 2022)
Objectives: To evaluate the knowledge and perceptions of dental students about Molar-Incisor Hypomineralization (MIH). Methodology: A semi-structured electronic questionnaire composed of 3 sociodemographic questions and 13 multiple-choice questions was applied to 80 undergraduate students from the School of Dentistry of the Federal University of Amazonas regularly enrolled in the fifth to a ninth period about the level of knowledge about diagnosis etiology and treatment of MIH, whose total score ranged from 1 to 36. The collected data were statistically analyzed, and the t-student, Shapiro-Wilk, Mann-Whitney, and chi-square tests were used to analyze quantitative and categorical data (p<0.05). Results: Of the respondents, 66.2% were female, and only 33.8% were male, with a median age of 23. Although 88.8% of the students claimed to know MIH and felt prepared (49.3%) to diagnose this enamel defect, there was a total lack of knowledge about its clinical characteristics. Genetic factors and chronic maternal and child diseases were necessary for the etiology of MIH. Finalist students were significantly more familiar with MIH (p=0.027), knew its clinical characteristics significantly better (p=0.001), and had already performed treatment in affected patients (p=0.039) when compared to beginners. Despite this, the average total score on the knowledge and perception of all students regarding MIH was 14. Conclusion: The general knowledge and perception of MIH among the participants were low, with the need for better clinical training and inclusion of the topic earlier during graduation.